Analysis of IT Service Quality on Attendance Application with ITIL V.4 Approach: A Case Study on CV. Syntax Corporation Indonesia - Komarudin Komarudin; Muhammad Hatta; Chairun Nas (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze the quality of Information Technology (IT) services in attendance applications with the ITIL V.4 approach in CV. Syntax Corporation Indonesia. The case study is used as a research approach to explore information related to the implementation of ITIL V.4 in improving the quality of IT services in the company's attendance application. The results of the study show that the implementation of ITIL V.4 can make a positive contribution in improving the quality of IT services in attendance applications at CV. Syntax Corporation Indonesia, with improved efficiency, reliability, and responsiveness of services. By implementing the ITIL V.4 approach, companies can improve the overall IT service management process, so that it can have a positive impact on the productivity and operational effectiveness of the company.